Using trees for soil improvement - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
Amelioration of Soil by Trees: A review of current concepts and practices / Prinsley, R.T. and M.J. Swift (eds.), 1986. Commonwealth Secretariat, London, 181 pp. ISBN 0 85092 300 X [workshop proceedings]